Clinical Ophthalmic Oncology Orbital Tumors - Perry, Julian D.; Singh, Arun D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Written by internationally renowned experts, Clinical Ophthalmic Oncology provides practical guidance and advice on the diagnosis and management of the complete range of ocular cancers. The book supplies all of the state-of-the-art knowledge required in order to identify these cancers early and to treat them as effectively as possible. Using the information provided, readers will be able to: · Provide effective patient care using the latest knowledge on all aspects of ophthalmic oncology. · Verify diagnostic conclusions based on comparison with numerous full-color clinical photographs from the authors' private collections, histopathologic microphotographs, imaging studies, and crisp illustrations. · Locate required information quickly owing to the clinically focused and user-friendly format. This volume describes the classification, differential diagnosis, and imaging of orbital tumors and discusses the most suitable treatment options for different tumor types.
Examination Techniques -- Classification of Orbital Tumors -- Differential Diagnosis in Child -- Differential Diagnosis in Adults -- Imaging Techniques -- Non-Specific Orbital Inflammation -- Orbital Vascular Tumors -- Benign Orbital Tumors -- Optic Nerve Tumors -- Lacrimal Gland Tumors -- Lacrimal Sac Tumors -- Orbital and Adnexal Lymphoma -- Malignant Orbital Tumors -- Orbital Rhabdomyosarcoma -- Enucleation for Ocular Tumors -- Orbital Exenteration -- Principles of Orbital Surgery -- Orbital Implants -- Ocular Prosthesis.
Keywords: Ophthalmology; Oncology .; Ophthalmology; Oncology